AN ANALYSIS OF ENGLISH TEACHER CODE SWITCHING AND CODE MIXING TO ENCOURAGE STUDENT ENGLISH LEARNING PARTICIPATION - Sudrajat; Usman Diennur; Anisa Septia Megawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the use of teacher code switching and code mixing in English classroom interaction and their role in encouraging student participation during the learning process. The research was conducted in Grade X AP 2 at SMK Mutiara Terpadu Palabuhanratu using a qualitative descriptive method with a case study approach. The participants consisted of one English teacher and the students of the selected class, five of whom were interviewed in depth. Data were collected through classroom observation, semi-structured interviews with the teacher and students, documentation, and transcription of classroom interaction, and were analyzed using thematic analysis. The findings show that the teacher employed three types of code switching—inter-sentential switching (119 utterances), intra-sentential switching (51 utterances), and extra-sentential switching (2 utterances)—as well as two types of code mixing, namely alternation (119 utterances) and insertion (53 utterances). These strategies were applied to explain learning materials, give instructions, overcome students’ language barriers, adapt language use to students’ proficiency levels, and maintain smooth classroom interaction. The results further reveal that teacher code switching and code mixing helped create learning conditions in which students could understand the material more easily, participate in discussions, answer and ask questions, follow instructions, and interact more confidently. Thus, teacher code switching and code mixing function as pedagogical communication strategies that support classroom interaction and encourage student participation in EFL learning.